"Sou feia, mas tô na moda" - o funk, discurso e discriminação (análise discursiva de documentário) - Borges, Roberto Carlos da Silva (2007)
The goal of the present work is to analyze, through the use of Semiolinguistics' theory of Patrick Charaudeu, the documentary film Sou feia, mas tô na moda" (I am ugly, but I m trendy), by Denise Garcia s. Using as main theoretical support the New Analysis of the Speech of Patrick Charaudeau (1996) and glancing over the notion of Ethos (Charaudeau: 2006 and Maingueneau: 2002), we intend to investigate the prejudice and discrimination that permeate funk music in the aforementioned documentary, and also on questions that refer to gender discrimination (specially regarding sexism) and social discrimination in our nation.